Pengaruh Integritas dan Profesionalisme terhadap Produktifitas Kerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Pasaman Barat - Tama Yourlanda, Bryan; Syamsir, Syamsir (Policy, Law and Political Research Center, 2023)
This study aims to see the influence of integrity and professionalism on employee work productivity. For this type of research, it is quantitative. Meanwhile, the sampling technique used is the yamane formula. As for the total population of employees, there are 69 people. The results showed that (1) There was a significant influence of integrity and professionalism variables on employee work productivity of 0.768 or 76.8%. (2) There is a partial significant influence of integrity variables on employee work productivity of 0.646 or 64.6%. (3) Professionalism has a significant effect on employee work productivity by 0.498 or 49.8%.